2012
DOI: 10.1099/mic.0.056119-0
|View full text |Cite
|
Sign up to set email alerts
|

NhaP1 is a K+(Na+)/H+ antiporter required for growth and internal pH homeostasis of Vibrio cholerae at low extracellular pH

Abstract: Vibrio cholerae has adapted to a wide range of salinity, pH and osmotic conditions, enabling it to survive passage through the host and persist in the environment. Among the many proteins responsible for bacterial survival under these diverse conditions, we have identified Vc-NhaP1 as a K + (Na + )/H + antiporter essential for V. cholerae growth at low environmental pH. Deletion of the V. cholerae nhaP1 gene caused growth inhibition when external potassium was either limited (100 mM and below) or in excess (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…The LSA1645 protein might have just such a regulatory role in maintaining internal pH, and we propose to name it NanP. It has recently been reported that in Vibrio cholerae, the NhaP1 described to be an K ϩ (Na ϩ )/H ϩ antiporter is required for growth and internal pH homeostasis (50). Although LSA1645 presents no homology with NhaP1, they could play similar roles.…”
Section: Discussionmentioning
confidence: 99%
“…The LSA1645 protein might have just such a regulatory role in maintaining internal pH, and we propose to name it NanP. It has recently been reported that in Vibrio cholerae, the NhaP1 described to be an K ϩ (Na ϩ )/H ϩ antiporter is required for growth and internal pH homeostasis (50). Although LSA1645 presents no homology with NhaP1, they could play similar roles.…”
Section: Discussionmentioning
confidence: 99%
“…In prokaryotes, Na + /H + antiporters are ubiquitous secondary transporters catalyze the efflux of intracellular alkali cations in exchange for external protons, which play a vital role in reducing the cytoplasmic concentration of toxic alkali cations and supporting Na + -dependent intracellular pH homeostasis under alkaline conditions1234. They were also designated Na + (Li + )/H + antiporters, due to Na + /H + antiport activity, together with Li + /H + antiport activity.…”
mentioning
confidence: 99%
“…1) (4). However, recent detailed biochemical characterization of NhaP-type antiporters NhaP-1 and NhaP-2 from Vibrio cholerae revealed that these antiporters mediate K ϩ /H ϩ exchange rather than Na ϩ /H ϩ exchange under physiological conditions (6,7). By analogy, we predict that the Y. pestis NhaP protein has a similar cation preference ( Fig.…”
mentioning
confidence: 99%